Perfil epidemiológico de pacientes amputados num hospital de referência brasileiro, 2012-2019 (Research, Society and Development, 2021)
Responsible for high rates of morbidity and mortality, amputation has constituted a great public health problem, which burdens the social security costs and the health system. We aimed to describe the epidemiological profile of people who suffered amputation in a public hospital in the interior of Brazil, which is a reference for a macroregion.This was a retrospective and descriptive epidemiological study, carried out by analyzing the medical records of 214 patients who underwent amputations of various causes, between the years 2012 and 2019 at the Municipal Hospital Dr. Raimundo Gobira, located in Teófilo Otoni, Minas Gerais, Brazil. Statistical analysis of Pearson's correlation, mean and standard deviation was performed. A significance level of 5% was adopted. Of the 214 cases of amputations, the majority were men (91.12%), aged 19-30 years (21.96%), from the urban area (63.45%). Of these, 46.26% were associated with work. The maquita was the tool responsible for most injuries (17.35%). The fingers of the left hand were the main body segments affected (23.60%). Most of the subjects were residents of Teófilo Otoni (34.57%). Approximately 20.10% of amputations occurred in the year 2018. Statistical significance was not demonstrated when age and length of hospital stay were correlated, although the results point to a longer length of stay as age increases. The results made it possible to understand the epidemiological reality of the causes of amputations performed in the region and provide public managers with the opportunity to make decisions based on prevention.